Pengaruh Pendidikan Terhadap Minat Wirausaha Pariwisata Halal: A Bibliometric Analysis - Rifqya Azzahra Bastian; Aida Rachmiana; Cut Dian Fitri; Fitrah Afandi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to analyze the development of scientific literature on the influence of entrepreneurship education on entrepreneurial intention in the context of halal tourism. The study is motivated by the limited integration between entrepreneurship education and entrepreneurial intention within halal tourism, as well as the lack of comprehensive global mapping of this research area. Previous studies have largely been empirical and context-specific, with limited efforts to examine broader knowledge structures. This research employs a bibliometric analysis with a quantitative-descriptive approach using data sourced from Scopus. The analysis includes keyword co-occurrence, publication trends, author collaboration networks, and thematic clustering, visualized באמצעות VOSviewer software. The findings reveal that entrepreneurship education serves as the central theme and is strongly associated with entrepreneurial intention, particularly among tourism students. Psychological factors such as entrepreneurial feasibility and entrepreneurial desirability are identified as key determinants influencing entrepreneurial intention. Furthermore, the study highlights a shift in research trends from conceptual approaches toward more applied perspectives, including experiential learning and the integration of halal values. However, topics such as halal entrepreneurial awareness and halal entrepreneurial intention remain relatively underexplored and insufficiently integrated. In conclusion, entrepreneurship education plays a crucial role in fostering entrepreneurial intention in halal tourism, yet further efforts are needed to integrate halal values into educational frameworks and to conduct empirical studies for developing a comprehensive model of halal entrepreneurship.